1978
DOI: 10.1103/physrevb.18.3360
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior of the magnetic susceptibility of the uniaxial ferromagnet LiHoF4

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 22 publications
5
32
0
Order By: Relevance
“…A summary of the extracted values of H c are listed in Table I. In Figs. 3(c) and 3(d), we show that β H = 0.47 (8), which is close to the mean-field exponent of 0.5. Within the uncertainty of the fits, the critical exponent does not change on dilution.…”
Section: B Transverse Field Dependencesupporting
confidence: 71%
“…A summary of the extracted values of H c are listed in Table I. In Figs. 3(c) and 3(d), we show that β H = 0.47 (8), which is close to the mean-field exponent of 0.5. Within the uncertainty of the fits, the critical exponent does not change on dilution.…”
Section: B Transverse Field Dependencesupporting
confidence: 71%
“…1 both the real and imaginary parts of the susceptibility as a function of T for zero transverse field. x 0 ͑T ͒ diverges at T c 1.53 K, below which the Ho spins order ferromagnetically [14,15]. At the identical temperature, there is a sharp increase in x 00 ͑T ͒, most likely due to the motion of domain walls [16].…”
mentioning
confidence: 97%
“…Using renormalization group arguments, Larkin and Khmelnitskii [8] and Aharony [9] showed that d * = 3 is the upper critical dimension for mean-field critical behaviour in a dipolar ferromagnet. This observation led to significant experimental efforts to find the expected logarithmic corrections to mean-field theory in LiHoF 4 [10,11,12,13,14]. The demagnetization field also renders the ferromagnetic transition quite peculiar in the presence of dipolar interactions [4] as these oppose a uniform magnetization and leads to the formation of domains below the transition [5,15].…”
mentioning
confidence: 99%